2018
DOI: 10.1108/jhti-10-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Examining family cohesion’s influence on resort vacation satisfaction

Abstract: Purpose Although much satisfaction research examines the role of demographics, few examine the phenomena of family cohesion or travel party composition and the role they play in influencing satisfaction. Therefore, the purpose of this paper is to leverage the two to further understand satisfaction. Design/methodology/approach Data from 400 vacationing families were analyzed to examine the factors of family cohesion, activity satisfaction and overall vacation satisfaction. Findings Contrary to previous rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Both satisfaction and perceived value have shown to be useful predictors and antecedents of behavioral intentions (Cronin et al, 2000;McDougall and Levesque, 2000;Murphy, 2018;Petrick and Backman, 2002;Tamn, 2000). The compelling amount of studies regarding customer satisfaction outcomes in the service industry indicates a precedent positive relationship between customer satisfaction and repurchase intention (Anderson and Sullivan, 1993;Cronin and Taylor, 1992;Ihtiyar et al, 2018;Kivela et al, 1999;Gregory and Fu, 2018;Zeithaml et al, 1996). Additionally, Chen and Chen (2010) found that although both perceived value and satisfaction have a significantly direct positive effect on customer's behavioral intentions, the effect of experience quality was conversely insignificant on behavioral intentions.…”
Section: Impact Of Satisfaction and Perceived Value On Repurchase Intentionmentioning
confidence: 99%
“…Both satisfaction and perceived value have shown to be useful predictors and antecedents of behavioral intentions (Cronin et al, 2000;McDougall and Levesque, 2000;Murphy, 2018;Petrick and Backman, 2002;Tamn, 2000). The compelling amount of studies regarding customer satisfaction outcomes in the service industry indicates a precedent positive relationship between customer satisfaction and repurchase intention (Anderson and Sullivan, 1993;Cronin and Taylor, 1992;Ihtiyar et al, 2018;Kivela et al, 1999;Gregory and Fu, 2018;Zeithaml et al, 1996). Additionally, Chen and Chen (2010) found that although both perceived value and satisfaction have a significantly direct positive effect on customer's behavioral intentions, the effect of experience quality was conversely insignificant on behavioral intentions.…”
Section: Impact Of Satisfaction and Perceived Value On Repurchase Intentionmentioning
confidence: 99%
“…Travel companionship has a significant moderation effect on the relationship between MTE and behavioural intentions.Previous researchers have also linked travel companionships andMTEs with tourist well-being. For example,Gregory & Fu (2018) concluded that people who travel with family members enjoy enhanced overall well-being. A link was also identified between family size and well-being, with smaller families experiencing greater sense of wellbeing(Gregory & Fu, 2018).…”
mentioning
confidence: 99%
“…For example,Gregory & Fu (2018) concluded that people who travel with family members enjoy enhanced overall well-being. A link was also identified between family size and well-being, with smaller families experiencing greater sense of wellbeing(Gregory & Fu, 2018). It has been further shown that travel experiences are significantly influenced by activities which affect positive emotions(Olsson et al, 2013) Zhu and Fan (2018).…”
mentioning
confidence: 99%